Synthesis and characteristics of silica nano-particles using modified sol–gel method in microreactor - Fiona, W.M. Ling; Abdulbari, Hayder A.; Chin, Sim-Yee (Elsevier Ltd, 2020)
Sol-gel is one of the known and widely applied techniques in nano-particles synthesis. However, the conventional batch sol–gel method produces silica nano-particles with uneven shapes and wide size distribution. In the present work, silica nano-particles will be synthesized using a traditional sol–gel method and a modified sol–gel technique by creating a microfluidic reactor. A olydimethylsiloxane microreactor was first designed and fabricated using the direct writing method. The microfluidic reactor was designed with a micro-droplets generation junction where the reactants are mixed to generate droplets where each droplet as an independent reactor. The synthesis process involved tetraethyl orthosilicate as a precursor, acetic acid as a catalyst and water as a hydrolysing agent. Transmission electron microscopy (TEM) was used to measure and evaluate the nano-particles size and distribution of the two sol–gel methods implemented. The silica nano-particles synthesized from conventional bench-scale sol–gel method showed poor monodispersity and not in a perfect spherical configuration that has an average size of 95 ± 4 nm. In contrast, highly monodispersed silica nano-particles were produced using a microreactor with an average size of 6 ± 1.3 nm, and the particles were in a perfect spherical configuration. The nano-particles produced from microflow system showed a reduction of 93.68% in size. The results indicated clearly that the micro-mixing associated with the micro-droplets generation is dynamically controlling the shape and size of the formulated nano-particles by controlling the droplet’s internal mixing mechanism.